Construção e validação de uma escala de esgotamento mental em médicos da linha de frente da Covid-19 - Ruviaro, Nathália (2022)
Physicians are constantly faced with death and difficult decisions that can affect their physical and psychological well-being. They represent an at- risk group, especially in the context of the pandemic COVID -19. The aim of the present study was to construct and validate the Mental Exhaustion Scale (EMS) using item response theory (IRT) and to analyze the dynamics of selfefficacy in relation to mental exhaustion. A quantitative cross-sectional study was conducted in five steps, starting with the literature review for the construction of the 37 items of the first version of the scale. After evaluation by three experts, 9 items were excluded. 310 experts participated in the survey. The dimensionality was checked by the analysis of the political factor, which was completed with the TRI. The data were fed to the Samejima Scaled Response Model. Levels of description were confirmed for 24 items. Moderately negative dynamics (r = -0.36) with self-efficacy (p < 0.01) were found, supporting the validity of the constructed instrument. It was concluded that the instrument, the Mental Exhaustion Scale with the final version of 24 items, provided evidence of validity, confirmed in both content and internal structure, and that individuals with higher self-efficacy are less likely to develop mental exhaustion.